2018
DOI: 10.1021/acssuschemeng.7b04768
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of Nutrients in Hydrochar Produced from Hydrothermal Carbonization of Poultry Litter under Different Treatment Conditions

Abstract: In this study, the effects of operating parameters on the behavior of nutrients during hydrothermal carbonization (HTC) of poultry litter (PL) were investigated. A number of HTC experiments were carried out using PL at different treatment temperatures, residence times, and initial pH. The standard measurement and testing protocol was adapted to determine the phosphorus (P) species in the solid hydrochar (HC), while the Ca, K, Mg, Na, Al, Zn, Mn, Fe, Cu, Cr, and Pb contents in each fraction were quantified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…This result suggests that the SP was more sensitive to reaction temperature compared to EP. In general, the reduction of SP and EP might be caused by the formation of non-apatite P and apatite P. This inference has been verified in prior studies [ 24 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This result suggests that the SP was more sensitive to reaction temperature compared to EP. In general, the reduction of SP and EP might be caused by the formation of non-apatite P and apatite P. This inference has been verified in prior studies [ 24 , 49 , 50 ].…”
Section: Resultssupporting
confidence: 72%
“…In general, the surface pores of hydrochars would increase with the rise of reaction temperature. On the one hand, with the increase in reaction temperature, the hydrochar matrix had strong adsorption to K, also promoting the formation of a more stable K [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Upon the addition of an alkaline BC to soil, the contribution of these cations and their subsequent exchange with Al 3+ and H + on the negative charge sites in the soil result in an increase in soil pH (Hailegnaw et al 2019). This liming effect can be inferred for HC as well, since numerous studies have found HC from various feedstocks to contain appreciable quantities of these (and other) macronutrients, depending on the HTC process conditions (Dieguez-Alonso et al 2018;Ghanim et al 2018;Puccini et al 2018;Reza et al 2013).…”
Section: Soil Phmentioning
confidence: 95%
“…The mixture was then centrifuged at 4000 tours/min for 15 min and filtered using 0.45 µm filters as described by (Ghanim et al 2018) and their concentration was calculated as the average of three determination.…”
Section: 2feedstock and Products Characterizationmentioning
confidence: 99%